Transferrin promotes fatty acid oxidation and liver tumor growth through PHD2-mediated PPARα hydroxylation in an iron-dependent manner - Xu Qian; Qimin Zhou; Yuan Ouyang; Xiaohong Wu; Xue Sun; Shuo Wang; Yuran Duan; Zhiqiang Hu; Yueru Hou; Zheng Wang; Xiaohan Chen; Katherine L. Wang; et al. (Proceedings of the National Academy of Sciences, 2025)
Tumor cells reshape iron and lipid metabolism for their rapid proliferation. However, how tumor cells coordinate the interplay between tumor cell–specific iron homeostasis and lipid metabolism reprogramming to counteract energy shortages remains unclear. Here, we demonstrated that glucose deprivation in hepatocellular carcinoma (HCC) cells induced AMPK-dependent Transferrin S685 phosphorylation, which exposed Transferrin nuclear localization signal (NLS) for binding to importin α7 and subsequent nuclear translocation. Nucleus-translocated Transferrin interacts with PPARα and enhance its protein stability to increase fatty acid oxidation (FAO) upon glucose deprivation. Mechanistically, PPARα-associated Transferrin upregulates iron-dependent PHD2-mediated PPARα P87 hydroxylation and subsequently disrupts the binding of MDM2 to PPARα, therefore inhibiting MDM2-mediated PPARα ubiquitination and degradation. Reconstitution of Transferrin S685A and NLS mutation or knock-in expression of PPARα P87A inhibited PPARα-mediated FAO upon energy stress, enhanced HCC cell apoptosis, and impeded liver tumor growth in mice. Importantly, combined treatment with Transferrin pS685 blocking peptide suppressing AMPK-Transferrin-PPARα axis could synergize with a well-established AMPK activator Metformin to inhibit tumor growth. Additionally, Transferrin pS685-mediated PPARα P87 hydroxylation is positively correlated with PPARα expression levels in human HCC specimens and poor patient prognosis. These findings revealed a mechanism by which Transferrin can sense energy stress to promote the hydroxylation and protein stability of PPARα through iron-dependent activation of PHD2 and underscore the moonlighting function of Transferrin in lipid catabolism and liver tumor development.